Efek Daun Kelor (Moringa Oleifera) Terhadap Produksi ASI - Fransiska Mochtar (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Breast Milk (ASI) is the primary source of nutrition for infants and provides long-term health benefits. However, some mothers experience insufficient breast milk production. Moringa leaves (Moringa oleifera) are known as a natural galactagogue that can enhance breast milk production. This study aims to evaluate the effectiveness of moringa leaves in increasing breast milk production through a systematic literature review and meta-analysis. Literature searches were conducted in the PubMed, Scopus, and Cochrane Library databases using relevant keywords. The meta-analysis results showed that moringa leaf supplementation significantly increased breast milk volume and prolactin levels compared to the control. However, further research is needed to evaluate its mechanism of action and long-term safety.